Pyk2 modulates hippocampal excitatory synapses and contributes to cognitive deficits in a Huntington’s disease model - Albert Giralt (Nature Portfolio, 2017)
Several kinases regulate spine morphology and plasticity. Here, the authors show that the tyrosine kinase Pyk2 regulates hippocampal plasticity and contributes to cognitive and hippocampal plasticity deficits in a mouse model of Huntington’s disease.